(S)‐(−)‐(2‐MeBu)N(Pr)2MeI Salt as Template in the Enantioselective Synthesis of the Enantiopure Two‐dimensional (S)‐(−)‐(2‐MeBu)N(Pr)2Me[ΛMnΔCr(C2O4)3] Ferromagnet. Issue 8 (25th June 2013) - Gruselle, Michel; Li, Yanling; Ovanesyan, Nikolay; Makhaev, Viktor; Shilov, Gennadi; Mushenok, Fedor; Train, Cyrille; Aldoshin, Serguey
ABSTRACT We describe herein the synthesis of (rac)‐ or enantiopure (S)‐(−)‐(2‐MeBu)N(Pr)2MeI ammonium salts. These racemic and enantiopure ammonium salts were used as cationic templates to obtain new two‐dimensional (2D) ferromagnets [(rac)‐(2‐MeBu)N(Pr)2Me][MnCr(C2O4)3] and [(S)‐(−)‐(2‐MeBu)N(Pr)2Me][ΔMnΛ nCr(C2O4)3]. The absolute configuration of the hexacoordinated Cr(III) metallic ion in the enantiopure 2D network was determined by a circular dichroism measurement. The structure of [(2‐MeBu)N(Pr)2Me][MnCr(C2O4)3], established by single crystal X‐ray diffraction, belongs to the chiral P63 space group. According to direct current (dc) magnetic measurements, these compounds are ferrromagnets with a temperature Tc = 6°K. Chirality 25:444–448, 2013. © 2013 Wiley Periodicals, Inc.